Cryptography and network security : principles and practice - Stallings, William (Boston : Prentice Hall, 2011)
It provides a practical survey of both the principles and practice of cryptography and network security, it explores the network security capability by providing a tutorial and survey of cryptography and network security technology.
Includes bibliographical references (p. 735-743) and index.
uaj 2/12/2013
Loans
Keywords: Computer networks -- Security measures; Data encryption (Computer science); Coding theory; Computer security